2021
DOI: 10.3390/pharmaceutics13050730
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Preferences for Oral Dosage Forms and Their Involvement in Formulation Research via EPTRI (European Paediatric Translational Research Infrastructure)

Abstract: The paucity of evidence-based data on formulation characteristics preferred by the children is known to limit the design of tailored paediatric dosage forms. The European Paediatric Translational Research Infrastructure (EPTRI) commissioned a study to evaluate children’s dosage forms perceived preferences in some European countries and explore the feasibility of using the young persons advisory groups (YPAGs) to involve children in formulation research. An online, age-adapted survey was developed and translate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…As reported by Saito et al [17], parents and nurses often dissolve or disperse powder formulations in water for children. Alessandrini et al also reported that liquid formulations were widely selected by children less than 12 years and granules were not appreciated, particularly by adolescents [18]. In this study, many parents also dispersed the fine granules in water and administered them.…”
Section: Discussionmentioning
confidence: 69%
“…As reported by Saito et al [17], parents and nurses often dissolve or disperse powder formulations in water for children. Alessandrini et al also reported that liquid formulations were widely selected by children less than 12 years and granules were not appreciated, particularly by adolescents [18]. In this study, many parents also dispersed the fine granules in water and administered them.…”
Section: Discussionmentioning
confidence: 69%
“…The main issues and concerns regarding the use of the most common pediatric solid and liquid dosage forms are summarized in Figure 4. In this regard, the European Paediatric Translational Research Infrastructure (EPTRI) project commissioned a case study aimed at collecting information about children and adolescents' experiences and preferences for oral dosage forms across various European countries (the United Kingdom, Italy, Spain, Albania, Romania, the Netherlands, the Dutch-speaking part of Belgium, Czech Republic, and Sweden) [41]. Overall, liquids were the most used and favored dosage forms.…”
Section: Appropriate Medications For Pediatrics: the Paradigm Shift T...mentioning
confidence: 99%
“…On the contrary, tablets and capsules, were mostly chosen by adolescents and children taking medicines more frequently. Granules were the last option among adolescents, thus resulting in the least appreciated formulation together with the oro-dispersible films, probably due to the lack of In this regard, the European Paediatric Translational Research Infrastructure (EPTRI) project commissioned a case study aimed at collecting information about children and adolescents' experiences and preferences for oral dosage forms across various European countries (the United Kingdom, Italy, Spain, Albania, Romania, the Netherlands, the Dutch-speaking part of Belgium, Czech Republic, and Sweden) [41]. Overall, liquids were the most used and favored dosage forms.…”
Section: Appropriate Medications For Pediatrics: the Paradigm Shift T...mentioning
confidence: 99%
“…The ability of children to swallow oral dosage forms causes great concerns in terms of medication adherence according to Lopez et al Hence chewable tablets imitating flavour gummy sweets are expected to improve paediatric patient adherence and dose palatability [ 22 ]. According to various studies in paediatric populations, chewable tablets are preferred for children from 5–12 years but they are also attractive for adolescents from 10–19 years old [ 23 ].…”
Section: Resultsmentioning
confidence: 99%